Methodik der S3-Leitlinien für alkohol- und tabakbezogene Störungen - Hoch, Eva; Mann, Karl (Der Nervenarzt, 2016)
Background: From 2010 until 2015 two interdisciplinary evidence-based guidelines were developed to summarize the current knowledge regarding screening, diagnostics and treatment of alcohol and tobacco-related disorders. Methods: Both guidelines were prepared under the auspices of the German Society for Psychiatry, Psychotherapy and Psychosomatics (Deutsche Gesellschaft für Psychiatrie, Psychotherapie, Psychosomatik und Nervenheilkunde, DGPPN) and the German Society for Addiction Research and Therapy (Deutsche Gesellschaft für Suchtforschung und -therapie, DG-Sucht). To meet the methodological criteria for the highest quality guidelines (S3 criteria) as defined by the Association of the Scientific Medical Societies in Germany (Arbeitsgemeinschaft der Wissenschaftlichen Medizinischen Fachgesellschaften, AWMF) the following criteria were realized: (1) a systematic search, selection and appraisal of the international literature, (2) a structured process to reach consensus and (3) inclusion of all relevant representatives of future guideline users. Results: More than 60 clinical experts and researchers analyzed the scientific literature. In total 41 international and national guidelines (23 for alcohol and 18 for tobacco) were used. Moreover, 83 systematic Cochrane reviews (alcohol 28, tobacco 55) and 5863 articles (alcohol 2213, tobacco 3650) were analyzed. A total of 7 expert groups formulated 174 recommendations for the screening, diagnosis and treatment of alcohol-related disorders. Six expert groups created 81 recommendations for the screening, diagnosis and treatment of tobacco-related disorders. Approximately 50 scientific associations, professional organizations, patient and family initiatives, as well as representatives of the healthcare system formed a consensus group. In seven 1 and 2-day conferences, all clinical recommendations were discussed and approved by this group. Both guidelines will be revised on a regular basis to guarantee that the clinical recommendations are kept up to date. Conclusions: Both systematically developed, evidence-based treatment guidelines are comprehensive instruments to provide orientation and assist the decision-making process for physicians, psychologists and other therapists as well as patients and their families in the diagnosis and treatment of alcohol and tobacco use related disorders.